Morgenthau, law and realism / Oliver Jütersonke. - Jütersonke, Oliver (Cambridge University Press, 2010)
Although he is widely regarded as the 'founding father' of realism in International Relations, this book argues that Hans J. Morgenthau's legal background has largely been neglected in discussions of his place in the 'canon' of IR theory. Morgenthau was a legal scholar of German-Jewish origins who arrived in the United States in 1938. He went on to become a distinguished professor of Political Science and a prominent commentator on international affairs. Rather than locate Morgenthau's intellectual heritage in the German tradition of 'Realpolitik', this book demonstrates how many of his central ideas and concepts stem from European and American legal debates of the 1920s and 1930s. This is an ambitious attempt to recast the debate on Morgenthau and will appeal to IR scholars interested in the history of realism as well as international lawyers engaged in debates regarding the relationship between law and politics, and the history of International Law.